Analyzing foot care practices and diabetes management: a cross-sectional KAP study in a tertiary care hospital - Alshahrani, Asma Malawi; Vasudevan, Rajalakshimi; Aldahish, Afaf; Alghazwani, Yahia; Shorog, Eman; Manusri, N.; Dhurke, Rajeshri; Chowdary, Puvvada Ranadheer; Devanandan, Praveen (Frontiers in Endocrinology, 2025)
IntroductionDiabetic foot complications, including foot ulcers and amputations, are significant contributors to morbidity and healthcare costs worldwide. Effective prevention requires comprehensive knowledge, positive attitudes, and consistent practices regarding foot care among diabetes patients. This study evaluates the Knowledge, Attitudes, and Practices (KAP) of diabetic patients in a tertiary care hospital setting to identify gaps and inform targeted interventions.MethodologyA cross-sectional study was conducted among 704 diabetes patients between January 2024 to September 2024 in a tertiary care hospital. A validated 20-item questionnaire assessed sociodemographic details, knowledge, attitudes, and practices regarding foot care. Descriptive statistics and logistic regression analysis were performed using SPSS to identify predictors of good foot care practices.ResultsThe study revealed moderate knowledge levels (mean score: 6.5 ± 1.8), with 54.1% of participants recognizing the importance of daily foot inspections. Positive attitudes were seen in 75.6%, but only 60.8% reported regular foot inspections, and 27% consulted healthcare professionals for foot care. Education level significantly influenced KAP outcomes, with participants having higher education showing better scores (p < 0.001). Longer diabetes duration (>10 years) was associated with improved practices (OR: 1.9; p = 0.01).The findings highlight critical gaps in knowledge and practice, especially among less-educated and newly diagnosed patients. Educational interventions and improved access to podiatric care are necessary to address these disparities. Strategies like community-based programs and telemedicine can enhance awareness and adoption of preventive measures, particularly in underserved areas.ConclusionEnhancing foot care knowledge and practices among diabetes patients is vital to reducing the burden of diabetic foot complications. Targeted education and access to healthcare services are essential components of comprehensive diabetes management.